Different risk factors for three major recurrence patterns of pathological stage II or III gastric cancer patients who completed adjuvant S-1 monotherapy. Issue 12 (December 2021) - Kano, Yosuke; Ohashi, Manabu; Muneoka, Yusuke; Takahari, Daisuke; Chin, Keisho; Yamaguchi, Kensei; Ida, Satoshi; Kumagai, Koshi; Makuuchi, Rie; Sano, Takeshi; Nunobe, Souya
Abstract: Introduction: After curative gastrectomy followed by 1-year adjuvant S-1 monotherapy for pathological stage (pStage) II or III gastric cancer, some patients experience peritoneal, hematogenous, or lymph nodal recurrence. However, risk factors for each recurrence pattern despite completed adjuvant S-1 monotherapy remain unclear. The aim of this study was to determine which factors influence each recurrence type after curative gastrectomy followed by 1-year adjuvant S-1 monotherapy. Materials and methods: A total of 380 patients with pStage II or III gastric cancer who completed 1-year adjuvant S-1 monotherapy after R0 gastrectomy between January 2008 and December 2013 were enrolled in this study. The risk factors that were associated with peritoneal, hematogenous, and lymph nodal recurrence were investigated by univariate and multivariate analyses. Results: Eighty (21.1%) of 380 patients developed recurrence. As the first site, peritoneal, hematogenous, and lymph nodal recurrence occurred in 42 (11.1%), 26 (6.8%), and 12 (3.2%) patients, respectively. In multivariate analysis, peritoneal metastasis was associated with signet ring cell carcinoma ( P < 0.001), pT4 ( P = 0.001), and pN3 ( P < 0.001), while hematogenous recurrence was associated with pN3 ( P = 0.019) and later initiation of S-1 (P = 0.013), and lymph nodal recurrence was associated with pN3 ( P = 0.002). Conclusion: The risk factors for peritoneal, hematogenous, and lymph nodal recurrence in pStage II or III gastric cancer patients who complete adjuvant S-1 monotherapy differ. This information may be helpful for daily surveillance of recurrence in post-operative and chemotherapeutic patients. Furthermore, it may be a useful reference to develop novel perioperative chemotherapy.